TRANSMISSION BELTS PERFORMANCE IN NORMAL AND HEAVY-DUTY CONDITIONS - MADALINA IGNAT; BOGDAN RUSU; ANDREI DUMITRU; ROXANA CONSTANTINESCU; CIPRIAN CHELARU (Journal of Engineering Studies and Research)
The main purpose of this article was to study the behavior of vehicle transmission belts in conditions similar to real ones, which can appear during their use. Transmission belts can be classified into several categories, but depending on their function, can be belts that work in dry conditions or immersed in oil. In this study, were analyzed both types of transmission belts. The samples were subject to different physical-mechanical tests: determination of hardness, density, thickness, abrasion, flex resistance, tensile strength and percentage extension and also to various conditions like, high and low temperature, immersion in liquids (oil, toluene, diesel). All the tests were performed before and after exposure, according to actual standards in ICPI accredited laboratory. Microscopy studies were done before and after the exposure to various factors, in order to appreciate the damage degree. Also, chemical specific analyses were made for determining the transmission belts composition. The findings from this study provide important insights into the behavior of transmission belts under different operating conditions.